ESTADO LAICO E DIREITOS HUMANOS FUNDAMENTAIS: UMA ANÁLISE DA RELATORIA DO PL 580 2007 E DE SUAS PALAVRAS QUE SANGRAM (Interdisciplinary Studies Journal, 2024)
This work aims to analyze the speech of Federal Deputy and Pastor Francisco Eurico da Silva, serving as the rapporteur for Bill No. 580/2007. In his report, he recommends rejecting the bill on its merits and supports the approval of Bill PL 5,167/2009, which asserts that relationships between same-sex individuals should not be equated to marriage, stable unions, or family entities. The methodology employed involved bibliographic and documentary research, gathering scientific articles, dissertations, and theses on the fundamental human rights related to sexual and gender diversity and same-sex marriage. This also included a review of pertinent legislation, notably the Federal Constitution of 1988 and the American Convention on Human Rights. The research aims to demonstrate how the progression of conservative agendas in the National Congress often incorporates moral and religious views to underpin speeches characterized by institutional discrimination. Such discrimination tends to marginalize, harm, and endanger marginalized groups. This sociopolitical scenario reflects a form of LGBTphobia that is deeply rooted in biblical precepts, contradicting the secular nature of the Brazilian State. This is further exemplified by the hate speech of some parliamentarians who represent religious entities in their official capacities.
Keywords: Secular State; Same-sex marriage; Institutional discrimination